Breast Schwannoma - Vandana Dialani; Neely Hines; Yihong Wang; Priscilla Slanetz (Case Reports in Medicine)
Schwannomas arise from Schwann cells of the peripheral nerve sheath. The most common locations include the head, neck, and extensor surfaces of the extremities. Intramammary schwannomas are very rare and account for only 2.6% of schwannomas. A review of the English literature reveals 27 such cases of breast schwannoma. In this paper we describe another such rare case.